2020
DOI: 10.1111/aec.12862
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale genetic structuring in a group‐living lizard, the gidgee skink (Egernia stokesii)

Abstract: By constraining gene flow, group living and natal philopatry can result in fine-scale genetic structure. Although the genetic structure of some group-living lizards has been characterised, studies are few compared with those for group-living bird and mammal species. The Egerniinae group of lizards exhibits a high diversity of social structures, making it a useful group for comparative studies of genetic structure across a broader range of social taxa. A well-studied member of Egerniinae is Egernia stokesii, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In other words, variation exhibited by 2300 SNPs was sufficient to trace each individual to its habitat. While genetic structure of populations within 10 km has been reported in plants (Geng et al, 2009; Helsen et al, 2015; Hevroy et al, 2018; Kitamura et al, 2018), amphibians (Kobayashi et al, 2018), reptiles (Pearson et al, 2020), fish (Ciannelli et al, 2010) and mammals (Ziege et al, 2020), fine‐scale genetic structure for flying insects is rare. For example, a similar number of SNPs used to study ants (Boyle et al, 2019; Smith et al, 2019), beetles (Weng et al, 2021) and butterflies (MacDonald et al, 2020) identified meaningful genetic clusters between long‐distance populations that reflect their geographical isolation, but in these studies, populations within 10 km of each other were genetically hard to distinguish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, variation exhibited by 2300 SNPs was sufficient to trace each individual to its habitat. While genetic structure of populations within 10 km has been reported in plants (Geng et al, 2009; Helsen et al, 2015; Hevroy et al, 2018; Kitamura et al, 2018), amphibians (Kobayashi et al, 2018), reptiles (Pearson et al, 2020), fish (Ciannelli et al, 2010) and mammals (Ziege et al, 2020), fine‐scale genetic structure for flying insects is rare. For example, a similar number of SNPs used to study ants (Boyle et al, 2019; Smith et al, 2019), beetles (Weng et al, 2021) and butterflies (MacDonald et al, 2020) identified meaningful genetic clusters between long‐distance populations that reflect their geographical isolation, but in these studies, populations within 10 km of each other were genetically hard to distinguish.…”
Section: Discussionmentioning
confidence: 99%
“…Central to the IBD process is the assumption that gene flow is proportionally inversely affected by the distance between populations. At a small geographical scale, the signal of geographical isolation is often overwhelmed by more immediate, sometimes anthropogenic, environmental differences such as a rural‐to‐urban gradient (Ziege et al, 2020) or cohort characteristics (Kitamura et al, 2018; Pearson et al, 2020). Signals of IBD at a fine scale are often weak (Crookes & Shaw, 2016; Hevroy et al, 2018), or otherwise nonexistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Egerniini of Welch (1982), and the earlier Egernina of De Vis (1888), which need to be treated as independent due to the different stems employed in the formation of the names, apply to a much more geographically restricted (Australia, the Solomon Islands, New Guinea and the Maluku Archipelago of Indonesia) and less species-rich (62 species in 8 genera) lineage for which there have been many fewer uses of the terms Egerniini/Egerninae/Egernidae (although again the informal name Egernia group of Greer (1979) has a much greater usage). While I have been able to identify 40 uses of these names (with or without the double -i) since Welch (1982) created Egerniini (Egerniidae: Hedges & Conn 2012;Pyron et al 2013;Zug 2013;Hedges 2014;Sy 2015;Bahmani et al 2016Bahmani et al , 2018Feizi et al 2016;Paluh & Bauer 2017;Čerňaňský et al 2020;Čerňaňský & Syromyatnikova 2021;Egerniinae: Hitchmough et al 2016;Bull et al 2017;Halliwell et al 2017a-c;Atkins et al 2018Atkins et al , 2020Foster et al 2018;Norval et al 2018Norval et al , 2021Bower et al 2019;Chapple et al 2019Chapple et al , 2021Ortiz et al 2019;Thorn et al 2019Thorn et al , 2021Treilibs et al 2019;While et al 2019;Norval & Gardner 2020;Pearson et al 2020;Ridley et al 2020;Stampe et al 2020;Thompson et al 2020;Watson et al 2020…”
Section: Relative Priority Of Some Names In the Family Groupmentioning
confidence: 99%
“…The influence of group living and natal philopatry on fine‐scale genetic structure in this same species was explored by Pearson et al . (2020) reporting that fine‐scale structure is present. Another member of the sub‐family Egerniinae, Liopholis slateri, was the subject of Ridley et al .’s (2020) study of communal burrows in relation to soil and vegetation.…”
mentioning
confidence: 99%